Radiosensitization characteristic of superparamagnetic iron oxide nanoparticles in electron beam radiotherapy and brachytherapy. (June 2019) - Rahman, WN; Kadian, SNM; Ab Rashid, R; Abdullah, R; Abdul Razak, K; Pham, BTT; Hawkett, BS; Geso, M
Abstract: Superparamagnetic Iron Oxide Nanoparticles (SPIONs) has been the focus in medical imaging as MRI contrast agents. SPIONs demonstrate intriguing properties that not only advantageous in diagnostic imaging but also for therapeutic application. In this study, the radiosensitization characteristic of SPIONs in electron beam radiotherapy and brachytherapy were investigated. This study was conducted in-vitro using HeLa cells with SPIONs (15 nm) concentration of 1, 2 and 3 mMol/L. Irradiations were done at doses ranging from 0 to 10 Gy using electron beams of energy 6 and 12 MeV as well as 0.38 MeV 192 Ir brachytherapy source. Cell survivals were determined from clonogenic assay. Radiosensitization characterization was performed by analyzing the sensitization enhancement ratio (SER) expolated from the survival curves. The results show SPIONs induce radiosensitization effects in electron beams especially at lower energy with SER value obtained up to 1.5. The radiosensitization is more prominent for brachytherapy with SER value around 2. Concentrations of SPIONs also play important roles in which higher SPIONs concentration are more likely to increase radiosensitization effects. In conclusion, radiosensitization are dependent on radiation energy and concentration of the SPIONs. Further characterization of the radiosensitization induced by SPIONs may enable clinical translation of SPIONs as radiosensitizer in radiotherapy.